A pico-satellite assembled and tested during the 6th CanSat Leader Training Program - Colín, Ángel (2017)
In this paper, we describe the process to construct a pico-satellite mounted in a bottle of polyethylene terephthalate (PET) of 345 ml. Theassembly and tests were made during the 6th CanSat Leader Training Program (CLTP-6) at University Hokkaido-Japan in the summer 2015. Thepico-satellite was launched in the facilities of Uematsu Electric Co. Ltd. in Akabira-Japan by a paper model rocket, which achieved a height ofapproximately 100 m. The mission was designed to measure physical variables, such as temperature and humidity using electronic sensors. Duringthe flight, we observed that the temperature inside the rocket was ∼0.5◦C higher than the temperature of the environment. We registered a humiditydifference of ∼5%, measured between the maximum height and the landing point. The flight pattern was projected to a plane that covers an areaof 50 m × 50 m by means the coordinates of a GPS.© 2016 Universidad Nacional Autónoma de México, Centro de Ciencias Aplicadas y Desarrollo Tecnológico. This is an open access article underthe CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).